Urbanisation in India - Purohit, Ashok (Jaipur, 2012)
About the Book: Urbanisation in India This substantive and unique role to the study of urbanization in India significantly analyses the powers and weaknesses of the Indian urban system and provides new insights into contemporary urban problems. The book focuses on the processes of urbanization and the nature of interdependence among urban centres and between urban centres and their hinterlands. The approach is at the macro level. The book gives an introduction of studies of urbanization in India. The several aspects of urbanization are covered in the chapters in this book which discuss the problem of defining an urban place, spatial patterns of urbanization classification of cities theories of settlement location and the analysis of settlement systems. Finally the author observes the basic issues involved in framing a national urbanization policy and expresses the hope that the development of smaller cities and towns may provide some relief from the problems of overcrowding and unplanned growth.
Keywords: Urbanization-India